Pemberian Supportive Educative System Tentang Otot Progresif Pada Keluarga Untuk Menurunkan Tekanan Darah Lansia Dengan Hipertensi - Rona Febriyona; Nur Uyuun I. Biahimo; Febrianto Adam (Jurnal Ventilator, 2023)
Introduction : Hypertension is a non-communicable disease which is a serious health problem because its prevalence continues to increase. Hypertension often does not show signs and symptoms, so it is often called the silent killer of death and is one of the main triggers for diseases such as heart disease, stroke and kidney disease. Method: Research design is a strategy used in research to achieve the goals of the researcher. The research design of the Nursing Final Scientific Work is pre-experimental with the pretest-posttests one group design approach. Results: showed that before giving Progressive Muscle, the blood pressure of Client 1 was 160/100 mmHg, Client 2 was 150/100 mmHg, and Client 3 was 180/100 mmHg. And after being given juice for 3 consecutive days, the blood pressure of client 1 was 130/100 mmHg, Client 2 was 130/90 mmHg, and Client 3 was 140/100 mmHg. Conclusion: The overall evaluation results after nursing actions are carried out, namely observing that the patient's blood pressure decreases, the patient can feel pain independently, as well as health education for patients and their families. Families can care for patients suffering from hypertension